Sensitive and selective detection of chloroform by current-voltage using ZnO nanorods modified electrode - Haslinda Abdul Hamid; Panapan Kunakornwattana; Norain Isa; Khairunisak Abdul Razak (Universiti Kebangsaan Malaysia, 2023)
The development of in situ chloroform detection is crucial due to the high risk of carcinogenic effects associated with chloroform exposure. In this study, an electrochemical-based chloroform sensor was fabricated using undoped ZnO nanorods on indium tin oxide (ZnONRs/ITO) electrode to detect chloroform in aqueous-phase samples. Based on the results, the FESEM imaging showed that the ZnONRs exhibited an evenly distributed circular structure with a diameter of 62-90 nm, while the EDX and XRD findings confirmed the presence of Zn and O elements deposited on the electrode surface. Furthermore, the phosphate buffer solution (PBS) solution significantly affected the performance of the modified electrode with an optimal concentration and pH of 0.1 M and pH 7. The results also highlighted the vital function of the modified ZnONRs/ITO electrode as an efficient electron mediator and its catalytic potential to induce chloroform oxidation. Most importantly, the modified ZnONRs/ITO electrode was able to detect the presence of chloroform in real seawater samples, where the repeatability and reproducibility tests achieved a Relative Standard Deviation (RSD) of 1.41% and 2.61%, respectively, indicating the exceptional performance of the modified electrode. Moreover, the modified ZnONRs/ITO electrode recorded a low limit of detection and high sensitivity of 1.50 μM and 2.11 μA/cm2·mM, respectively, within a 0.010-10 mM linear dynamic range. In conclusion, the current-voltage (I-V) method proved the reliable, satisfactory, and effective fabrication of the modified ZnONRs/ITO electrode for chloroform sensing in aqueous-phase samples, including in real seawater samples.